Charge site assignment in native proteins by ultraviolet photodissociation (UVPD) mass spectrometry. Issue 1 (24th November 2015) - Morrison, Lindsay J.; Brodbelt, Jennifer S.
Abstract : Characterization of all gas-phase charge sites of natively sprayed proteins and peptides is demonstrated using 193 nm UVPD. Abstract : Characterization of all gas-phase charge sites of natively sprayed proteins and peptides is demonstrated using 193 nm UVPD. The high sequence coverage offered by UVPD is exploited for the accurate determination of charge sites in protein systems up to 18 kDa, allowing charge site to be studied as a function of protein conformation and the presence of disulfide bonds. Charging protons are found on both basic sidechains and on the amide backbone of less basic amino acids such as serine, glutamine, and proline. UVPD analysis was performed on the 3+ charge state of melittin, the 5+ to 8+ charge states of ubiquitin, and the 8+ charge state of reduced and oxidized β-lactoglobulin. The location of charges in gas-phase proteins is known to impact structure; molecular modeling of different charge site motifs of 3+ melittin demonstrates how placement of protons in simulations can dramatically impact the predicted structure of the molecule. The location of positive charge sites in ubiquitin and β-lactoglobulin are additionally found to depend on the presence or absence of salt-bridges, columbic repulsion across the length of the peptide, and protein conformation. Charge site isomers are demonstrated for ubiquitin and β-lactoglobulin but found to be much less numerous than previously predicted.